ANALISIS PELAYANAN PADA KANTOR PERPUSTAKAAN ARSIP DAN DOKUMENTASI KABUPATEN SAROLANGUN - Lestari, Ida (Jurnal Dinamika Manajemen, 2015)
This study is entitled "Analysis of Services at the Archives and Documentation Library Office of Sarolangun Regency" which aims to see an overview of the services provided by the Archives and Documentation Library Office of Sarolangun Regency. This research is a qualitative descriptive study using a survey research method with 100 respondents, namely visitors to the Archives and Documentation Library Office in Sarolangun Regency. Data collection using a questionnaire anchored using a 5-point Likert scale. To analyze the data using a range of scales. The results of this study obtained an overview of services at the Archives and Documentation Library Office of Sarolangun Regency, the service procedure factor obtained an illustration that the service was very good, the service transparency factor obtained a good service description, the service efficiency factor obtained a very good service description, the service accuracy factor obtained a good service description and factors justice gets service obtained a picture of very good service. The main implication that can be recommended from this study is that the service transparency and accuracy factors are in the good service category, for this reason these two factors must receive attention from the Sarolangun Regency Archives and Documentation Library Office.